IDE in Nicaragua: quest for sustainability. Issue 1 (3rd January 2017) - Narapareddy, Vijaya L.; Sampson, Nancy; Vishwanath, S.R.
Abstract : Synopsis: International Development Enterprises (iDE), a non-profit organization, won numerous awards for its poverty alleviation efforts through the sale of low-cost irrigation technologies to the Base of Pyramid (BoP) farmers around the world. This case discusses iDE's entry into Nicaragua and the challenges this global social enterprise faced in bringing drip irrigation and other water technologies to the rural subsistence coffee farmers in Nicaragua. It presents the tough decisions it faced in 2012 regarding the future of its for-profit social business, iDEal Tecnologias, in Nicaragua. This case captures the tension in hybrid social enterprises. Research methodology: This case was developed through the following primary sources as well as some secondary sources. Primary: discussions with iDE's CEO Doerksen, Urs Heierli (Coordinator of iDE's operations in Nicaragua), and Skype conversations with iDEal Tec's Country Director, Nadja Kränzlin. Secondary: documents provided by the company and other publicly available sources. Relevant courses and levels: This case is intended for use in undergraduate, graduate, and executive courses in: social entrepreneurship, non-profit management, and managing sustainable businesses. It may also be used in the sustainability module of courses in international business/management/marketing, and business strategy and policy. It would be best to position this case toward the middle or latter half of the course as it is an integrative case that challenges students to evaluate the sustainability of a social enterprise from multiple perspectives. Theoretical bases: The theoretical bases for this case are: defining and implementing a sustainable strategy in hybrid social enterprises. Serving BoP customers with a vision of enabling prosperity.